2007
DOI: 10.1007/s00203-007-0297-7
|View full text |Cite
|
Sign up to set email alerts
|

The highly toxic oxyanion tellurite (TeO 3 2− ) enters the phototrophic bacterium Rhodobacter capsulatus via an as yet uncharacterized monocarboxylate transport system

Abstract: The facultative phototroph Rhodobacter capsulatus takes up the highly toxic oxyanion tellurite when grown under both photosynthetic and respiratory growth conditions. Previous works on Escherichia coli and R. capsulatus suggested that tellurite uptake occurred through a phosphate transporter. Here we present evidences indicating that tellurite enters R. capsulatus cells via a monocarboxylate transport system. Indeed, intracellular accumulation of tellurite was inhibited by the addition of monocarboxylates such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
42
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 30 publications
2
42
0
Order By: Relevance
“…The link between tellurite uptake and toxicity in bacterial cells has been previously discussed in a limited number of reports (2,3,7). In Escherichia coli, it was shown that mutations in a phosphate transport system confer a high level of resistance to tellurite and that the oxyanion competes very efficiently for 32 P i transport (7).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…The link between tellurite uptake and toxicity in bacterial cells has been previously discussed in a limited number of reports (2,3,7). In Escherichia coli, it was shown that mutations in a phosphate transport system confer a high level of resistance to tellurite and that the oxyanion competes very efficiently for 32 P i transport (7).…”
mentioning
confidence: 98%
“…Finally, in the phototrophic species Rhodobacter capsulatus it was suggested that a phosphate transporter might also be responsible for tellurite uptake (3). This hypothesis has recently been questioned because of the extremely high concentration of P i needed to significantly inhibit tellurite uptake (2). Conversely, acetate was found to decrease the uptake of tellurite, when present at concentrations as low as 1 M (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known concerning the biochemical interaction between microbial cells and tellurite although it has been suggested that tellurite exerts its toxic action in the cytoplasmic compartment by triggering an increase in the generation of reactive oxygen species (Borsetti et al 2005;Pérez et al 2007). This implies that the uptake of the oxyanion by the cell is a prerequisite for the full development of its toxicity although the link between tellurite uptake and toxicity in bacterial cells has only been investigated in a limited number of reports (Borghese et al 2008;Borsetti et al 2003;Tomás and Kay 1986;Turner et al 2007;Turner et al 1995).…”
mentioning
confidence: 98%
“…Notably, photosynthetic-anaerobically grown cells show a very high minimal inhibitory concentration (MIC) for tellurite ([800 lM) while dark-aerobically grown cells show an extremely low MIC for tellurite (%8 lM) (Borghese et al 2004). It was shown that intermediates of the TCA cycle such as malate, succinate or fumarate, when used as growth carbon sources, make the cells very sensitive to tellurite; conversely, other metabolites such as pyruvate or acetate drastically increase the MIC for the oxyanion by competing with tellurite for the same entry port (Borghese et al 2008), which has been identified as an acetate permease (ActP) (Borghese and Zannoni 2010).…”
mentioning
confidence: 98%